2018
DOI: 10.1007/s00261-018-1718-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of PI-RADSv2 and ADC parameters in differentiating Gleason pattern 3 + 4 and 4 + 3 prostate cancer

Abstract: ADC metrics could differentiate GP 3 + 4 from 4 + 3 PCa with high specificity and moderate accuracy while PI-RADSv2, did not differentiate between these patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…The ADC has shown an increased accuracy in addition to the DWI analysis in detection and localization of PCa (31). ADC map is a model that expresses the signal decay with increased b-value.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%
“…The ADC has shown an increased accuracy in addition to the DWI analysis in detection and localization of PCa (31). ADC map is a model that expresses the signal decay with increased b-value.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) maps derived from diffusion-weighted imaging (DWI) sequences are useful imaging markers to evaluate the aggressiveness of PCa non-invasively, and have repeatedly proven to be correlated with GS ( 19 21 ). Furthermore, ADC maps could differentiate GG2 from GG3 ( 22 , 23 ). Moreover, studies showed that ADC maps had the value of predicting GS upgrading ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 97%
“…Many authors affirm that the ADC ratio seems to be a more useful and reproducible method because it is independent of the diffusion parameters as selected b values and vector strength [ 21 - 24 ]. Nevertheless, a number of factors still limit ADCr’s efficacy.…”
Section: Discussionmentioning
confidence: 99%